FUNCTIONAL ORGANIZATIONS CONCEPT OF THE POLYTECHNIC UNIVERSITY TYPICAL INFORMATION RESOURCES INTERNET PORTAL (Journal of Information Technologies in Education (ITE), 2010)
Functional organizations concept of the polytechnic university typical information resources Internet portal are presented by subsystems, services, WEB-resources and information areas. Typical functional architecture of the university information resources Internet portal is showed.
Keywords: architecture; information resource; portal; service; sub-system; typical structure